2021
DOI: 10.1016/j.celrep.2021.109333
|View full text |Cite
|
Sign up to set email alerts
|

Altered conformation of α-synuclein drives dysfunction of synaptic vesicles in a synaptosomal model of Parkinson’s disease

Abstract: Altered conformation of a-synuclein drives dysfunction of synaptic vesicles in a synaptosomal model of Parkinson's disease Graphical abstract Highlights d Mutations in aSyn affect the biochemistry, architecture, and function of synapses d In-cell NMR reveals aSyn's participation in transient interactions at synapses d aSyn-synapse interactions depend on the integrity of synaptic components d The 3K mutation in aSyn reduces its ability to participate in synaptic interactions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…Moreover, we showed that transgenic (tg) expression in mice of the E46K mutation that causes PD and dementia with Lewy bodies (DLB), and especially expression of an engineered mutant with two additional E→K substitutions in the adjacent KTK E GV repeat motifs (E35K + E46K + E61K), can produce a striking PD-like motor phenotype with resting tremor and limb and gait deficits responding in part to L-DOPA 23 . These ‘tetramer-abrogating’ tg mice have nigral and cortical αSyn inclusions, increased αSyn pSer129 phosphorylation, decreased dopamine levels, disrupted synaptic ultrastructure, and lysosomal changes resembling those of human PD 16 , 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we showed that transgenic (tg) expression in mice of the E46K mutation that causes PD and dementia with Lewy bodies (DLB), and especially expression of an engineered mutant with two additional E→K substitutions in the adjacent KTK E GV repeat motifs (E35K + E46K + E61K), can produce a striking PD-like motor phenotype with resting tremor and limb and gait deficits responding in part to L-DOPA 23 . These ‘tetramer-abrogating’ tg mice have nigral and cortical αSyn inclusions, increased αSyn pSer129 phosphorylation, decreased dopamine levels, disrupted synaptic ultrastructure, and lysosomal changes resembling those of human PD 16 , 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise function of αSyn is still debated, it has become increasingly accepted that at least part of its function in neurons involves the regulation of vesicle trafficking, including during synaptic transmission, for example, by controlling the dilation of the exocytotic fusion pore 14 and chaperoning the assembly of SNARE complexes 15 , 16 . αSyn has long been considered a ‘natively unfolded’ protein in aqueous solution 17 and in cells 18 , despite the widely-replicated finding that unfolded recombinant αSyn readily adopts an α-helical conformation upon binding to the outside of certain highly curved lipid vesicles in vitro 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A study in 2018 analyzed human neuroblastoma SH-S5Y5 cells and found that both DA-induced oligomeric α-synuclein aggregates and α-synuclein PPFs lead to sequestered levels of VAMP-2 [ 34 ]. In line with this, another group detected decreased protein levels of VAMP2, syntaxin-1, and synaptophysin when exposed to overexpressed human WT α-synuclein in transgenic mice around 12 months old, as well as both the E46K and 3K α-synuclein mutations [ 43 ]. By contrast however, another group reported no changes in the levels of these proteins, despite also using human WT α-syn and a similar analysis technique [ 18 ].…”
Section: Resultsmentioning
confidence: 74%
“…Human post-mortem tissue that was obtained from PDD and DLB patients revealed reduced Rab3A expression levels with a loss of 24–34% identified via WB and a loss of 27–43% identified via the ELISA technique. The research also detected reduced levels in 3k mutant mice [ 43 ]. However by contrast, another group found a 1.3-fold increase in the Rab3a protein levels (30%) in transgenic mice that were expressing the A53T α-synuclein mutation [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Natively unfolded α-synuclein in solution, adopts an α-helical conformation in its N-terminal domain in the presence of membranes with acidic phospholipid headgroups and/or high curvature [ 34 36 ]. This interaction of α-synuclein with membranes may normally reduce misfolding into a β-sheet assembly [ 37 ] and/or promote physiological multimers [ 38 , 39 ] that mediate its function in SNARE complex assembly and synaptic vesicle recycling [ 40 ]. On the other hand, the presence of lipids and detergents was also shown to increase the rate of α-synuclein fibril formation [ 41 , 42 ].…”
Section: Initiation Of α-Synuclein Aggregation Entails Aberrant Membr...mentioning
confidence: 99%